Targeted Therapy in a Rare Spindle Cell Tumor with ETV6-NTRK3 Gene Fusion Rearrangement: A Case Report - da Silva, Jessé Lopes; Pires, Andréa Rodrigues Cordovil; Romeiro, Priscilla de Almeida; Caetano, Felipe de Carvalho; Fernandes, Carolina de Bustamante; Matedi, Sumara Abdo Lacerda; de Melo, Andréia Cristina (Brazilian Journal of Oncology, 2025)
Advances in genomic tools have significantly improved the classification of soft tissue tumors (STTs), enabling the identification of specific subsets characterized by recurrent fusions and genetic alterations involving the Raf-1 proto-oncogene, serine/threonine kinase (RAF1), B-Raf proto-oncogene, serine/threonine kinase (BRAF), and neurotrophic tyrosine receptor kinase (NTRK) genes. The present study aims to address the clinical challenge of diagnosing and managing a rare case of spindle cell tumor by examining the utility of molecular characterization, particularly focusing on NTRK rearrangements and their relationship with clinical outcomes. These tumors are defined by the coexpression of S100 and CD34 markers, lacking SOX-10 expression. Genetic changes can also be observed in STTs exhibiting spindle cell morphology, with fibroblastic or neural characteristics.The current report presents a rare case of a spindle cell tumor in a 15-year-old male patient. Comprehensive histopathological and molecular analyses revealed the tumor's distinct entity through the coexpression of S100 and CD34 markers and an unusual ETV6-NTRK3 gene rearrangement. The identification of the ETS variant transcription factor 6-neurotrophic receptor tyrosine kinase 3 (ETV6-NTRK3) gene fusion was critical for tailoring a personalized therapeutic approach using larotrectinib. Periodic imaging assessments during treatment demonstrated a significant tumor response, culminating in a complete metabolic response by fluorodeoxyglucose (FDG) positron-emission tomography-computed tomography (PET-CT).This rare case underscores the importance of precise diagnostic criteria and advanced molecular testing in effectively managing rare STTs. The identification of the ETV6-NTRK3 rearrangement facilitated a successful personalized treatment strategy, highlighting the need for interdisciplinary collaboration in patient care. Integrating genomic insights into clinical practice is essential for managing complex spindle cell tumors and improving patient outcomes.
Keywords: sarcomas; rare diseases; S100 proteins; tyrosine kinase inhibitors